Strategic and Ethical Considerations in Managing Digital Privacy - Sarathy, Ravi (Journal of business ethics, 2003)
Individualized customer information is at the heart of on-line commerce. Using increasing amounts of customer-specific data enhances the success and value of one-to-one on-line marketing; but the extensive gathering and use of data specific to individuals also causes alarm over the loss of digital privacy, setting up a confrontation between e-commerce and society. Governments and nations, particularly in Europe, have reacted with a reliance on sweeping laws governing digital privacy protection while other nations such as the U.S. have generally preferred to allow companies and industry associations to regulate themselves. This tenuous balance is under attack from both sides. In this paper, we set up a framework which incorporates the environmental context, ethical perspectives and firm-specific considerations to help firms develop a strategy for handling digital privacy concerns.